NATURAL RADIOACTIVITY OF THE CRYSTALLINE BASEMENT ROCKS OF THE PELORITANI MOUNTAINS (NORTH-EASTERN SICILY, ITALY): MEASUREMENTS AND RADIOLOGICAL HAZARD. Issue 4 (18th November 2020) - Romano, D; Caridi, F; Di Bella, M; Italiano, F; Magazù, S; Caccamo, M T; Tripodo, A; Faggio, G; Grillo, R; Triolo, C; Messina, G; Gattuso, A; et al.
Abstract: Crystalline rocks can produce dangerous radiation levels on the basis of their content in radioisotopes. Here, we report radiological data from 10 metamorphic and igneous rock samples collected from the crystalline basement of the Peloritani Mountains (southern Italy). In order to evaluate the radiological properties of these rocks, the gamma radiation and the radon emanation have been measured. Moreover, since some of these rocks are employed as building materials, we assess the potential hazard for population connected to their use. Gamma spectroscopy was used to measure the 226 Ra, 232 Th and 40 K activity concentration, whereas the radon emanation was investigated by using a RAD 7 detector. The results show 226 Ra, 232 Th and 40 K activity concentration values ranging from (17 ± 4) to (56 ± 8) Bq kg −1, (14 ± 3) to (77 ± 14) Bq kg −1 and (167 ± 84) to (1760 ± 242) Bq kg −1, respectively. Values of the annual effective dose equivalent outdoor range from 0.035 to 0.152 mSv y −1, whereas the gamma index is in the range of 0.22–0.98. The 222 Rn emanation coefficient and the 222 Rn surface exhalation rate vary from (0.63 ± 0.3) to (8.27 ± 1.6)% and from (0.12 ± 0.03) to (2.75 ± 0.17) Bq m −2  h −1, respectively. The indoor radon derived from the building use of these rocks induces an approximate contribution to the annual effective dose ranging from 8 to 176 μSv y −1 . All the obtained results suggest that the crystalline rocks from the Peloritani Mountains are not harmful for the residential population, even though they induce annual effective doses due to terrestrial gamma radiation above the worldwide average values. Moreover, their use as building materials does not produce significant health hazards connected to the indoor radon exposure.